Proton Transport in a Highly Conductive Porous Zirconium‐Based Metal–Organic Framework: Molecular Insight. Issue 12 (17th February 2016) - Borges, Daiane Damasceno; Devautour‐Vinot, Sabine; Jobic, Hervé; Ollivier, Jacques; Nouar, Farid; Semino, Rocio; Devic, Thomas; Serre, Christian; Paesani, Francesco; Maurin, Guillaume
Abstract: The water stable UiO‐66(Zr)‐(CO2 H)2 MOF exhibits a superprotonic conductivity of 2.3×10 −3  S cm −1 at 90 °C and 95 % relative humidity. Quasi‐elastic neutron scattering measurements combined with aMS‐EVB3 molecular dynamics simulations were able to probe individually the dynamics of both confined protons and water molecules and to further reveal that the proton transport is assisted by the formation of a hydrogen‐bonded water network that spans from the tetrahedral to the octahedral cages of this MOF. This is the first joint experimental/modeling study that unambiguously elucidates the proton‐conduction mechanism at the molecular level in a highly conductive MOF. Abstract : Proton conductivity : The superprotonic behavior of the water‐stable UiO‐66(Zr)‐(CO2 H)2 metal–organic framework (MOF) was examined at the molecular level by combining quasi‐elastic neutron scattering measurements and aMS‐EVB3 molecular dynamics simulations. The proton transport is shown to be assisted by the formation of a hydrogen‐bonded network of water molecules that spans from the tetrahedral to the octahedral cages of this MOF.